2022
DOI: 10.3389/fpubh.2022.956712
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity and temporal trend of liver cancer in China from 1990 to 2019 and predictions in a 25-year period

Abstract: ObjectiveThis study aims to reveal epidemiological features and trends of liver cancer (LC) in China.MethodsWe retrieved data from the Global Burden of Disease database 2019. Joinpoint regression was used to examine the temporal trend of LC. Future trends of LC were estimated using the Nordpred.ResultsThe incidence, mortality, and disability-standardized life year (DALY) rate of LC declined in China from 1990 to 2019. Among >210,000 LC cases in 2019, the LC incidences were nearly 3.15 times higher in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…As previously reported in South Korea and Taiwan China, the "lag effect" might account for the elevated disease burden in Mainland China, where the incidence of liver cancer among elderly hepatitis reservoirs remains high [15,30]. Yue et al found that the rate of elderly HCC patients increased by 55.9% in Mainland China over 3 decades, related deaths increased by 39.9%, and the corresponding disease burden increased by 31.4% [31]. Moreover, less than one-third of Chinese adults were reported to establish vaccine-mediated immunity for hepatitis virus, and these high-risk people might eventually contribute to the elevated disease burden of liver cancer in China [32].…”
Section: Introductionmentioning
confidence: 82%
“…As previously reported in South Korea and Taiwan China, the "lag effect" might account for the elevated disease burden in Mainland China, where the incidence of liver cancer among elderly hepatitis reservoirs remains high [15,30]. Yue et al found that the rate of elderly HCC patients increased by 55.9% in Mainland China over 3 decades, related deaths increased by 39.9%, and the corresponding disease burden increased by 31.4% [31]. Moreover, less than one-third of Chinese adults were reported to establish vaccine-mediated immunity for hepatitis virus, and these high-risk people might eventually contribute to the elevated disease burden of liver cancer in China [32].…”
Section: Introductionmentioning
confidence: 82%
“…BAPC and Nordpred models are commonly used in projecting disease burden [ 26 , 27 ]. We first validated the accuracy of the 2 models using data from 1990 to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The Nordpred and BAPC models were used to project the disease burden parameters from osteoarthritis by sex from 2020 to 2039 [ 26 ]. To evaluate the performance of the Nordpred and BAPC models, data from 1990 to 2019 were divided into 2 intervals (1990–2009 and 2010–2019).…”
Section: Methodsmentioning
confidence: 99%
“…The Nordpred method, widely recognized in scholarly discussions, is applied across Socio-demographic Index (SDI) regions and in 21 regional forecasting models globally. It employs age-period-cohort analysis to predict future disease trends, providing a structured framework for estimating future health scenarios based on historical data and demographic dynamics [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%